Pop Art - Cameron, Dan; Glenn, Constance W.; Kellein, Thomas; Livingstone, Marco; Maharaj, Sarat; Pacquement, Alfred; Weiss, Evelyn; de Grey, Roger; Museum Ludwig, Köln; Centro de Arte Reina Sofia, Madrid (London : Royal Academy of Arts, 1991)
Arman ; Arroyo, Eduardo ; Artschwager, Richard ; Barker, Clive ; Ben ; Bengston, Billy Al ; Blake, Peter ; Boshier, Derek ; Brecht, George ; Caulfield, Patrick ; César ; Christo ; D'Arcangelo, Allan ; Dine, Jim ; Equipo Cronica ; Filliou, Robert ; Goode, Joe ; Hains, Raymond ; Hamilton, Richard ; Hockney, David ; Indiana, Robert ; Jacquet, Alain ; Jess ; Johns, Jasper ; Johnson, Ray ; Jones, Allen ; Kaprow, Allan ; Kienholz, Edward ; Kitaj, R.B. ; Köpcke, Arthur ; Lichtenstein, Roy ; Maciunas, George ; Oldenburg, Claes ; Paik, Nam June ; Paolozzi, Eduardo ; Phillips, Peter ; Pistoletto, Michelangelo ; Polke, Sigmar ; Ramos, Mel ; Rauschenberg, Robert ; Raysse, Martial ; Richter, Gerhard ; Rivers, Larry ; Rosenquist, James ; Rotella, Mimmo ; Ruscha, Ed ; de Saint Phalle, Niki ; Segal, George ; Self, Colin ; Smith, Richard ; Spoerri, Daniel ; Thiebaud, Wayne ; Tilson, Joe ; Tinguely, Jean ; Villeglé, Jacques ; Vostell, Wolf ; Warhol, Andy ; Watts, Robert ; Wesley, John ; Wesselmann, Tom ; Westermann, Horace Clifford ; Williams, Emmett
biografie
Pop Art, Royal Academy of Arts, London, 13 september - 15 december 1991 ; Museum Ludwig, Köln, 23 january - 19 april 1992 ; Centro de Arte Reina Sofia, Madrid, 16 June - 14 September 1992
Engels
boek